Análise técnica e econômica entre veículos elétricos e veículos a combustão interna - Pangoni, Fabrício Cristiano; Pereira Silva, Ramon Eduardo (Latin American Journal of Energy Research, 2024)
This article presents a case study for a family living in the city of Campo Grande – MS in which a technical and economic comparative proposal is made between the use of internal combustion vehicles (VCI) and electric vehicles (EV), 2023 models, in 4 different categories. Case 1 involves the analysis of the Fiat Mobi Like and Jac e-JS1 subcompacts. Case 2, the compact Hyundai HB20 Sense and Peugeot E-208 GT. Case 3, the midsize Nissan Versa Sen-se and BYD Dolphin GS 180EV. Case 4 for the large Nissan Leaf Tekna and Toyota Corolla Cross XR 20. The hypotheses of using or not using a photovoltaic system connected to the grid (SFVCR) and 3 scenarios based on the daily distance covered by the EV are analyzed, being 10